2022
DOI: 10.1088/1674-1056/ac3a5f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical design of thermal spin molecular logic gates by using a combinational molecular junction

Abstract: Based on the density functional theory combined with the non-equilibrium Green’s function methodology, we have studied the thermally-driven spin-dependent transport properties of a combinational molecular junction consisting of a planar four-coordinate Fe molecule and a 15,16-dinitrile dihydropyrene/cyclophanediene molecule with single-walled carbon nanotube bridge and electrode. Our results show that the magnetic field and light can effectively regulate the thermally-driven spin-dependent currents. Perfect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[13][14][15][16][17][18] In experiment, Sierra et al have detected the thermoelectric spin voltage due to the thermally driven spin-polarized currents in the FM graphene nanoribbons. [19] In theory, Zhao et al employed planar four-coordinate Fe complexes-based molecular, [20] Mn-porphyrin trimer molecular, [21] Mn ph-thalocyanine molecular, [22,23] and a hybrid molecular junction comprising a planar four-coordinate Fe molecule and a 15,16dinitrile dihydropyrene/cyclophanediene molecule [24,25] to construct thermal spin molecular Boolean logic gates like AND, NOT, XOR, and OR. All these thermal spin molecular Boolean logic gates contain metal atoms, providing the magnetic source of the devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] In experiment, Sierra et al have detected the thermoelectric spin voltage due to the thermally driven spin-polarized currents in the FM graphene nanoribbons. [19] In theory, Zhao et al employed planar four-coordinate Fe complexes-based molecular, [20] Mn-porphyrin trimer molecular, [21] Mn ph-thalocyanine molecular, [22,23] and a hybrid molecular junction comprising a planar four-coordinate Fe molecule and a 15,16dinitrile dihydropyrene/cyclophanediene molecule [24,25] to construct thermal spin molecular Boolean logic gates like AND, NOT, XOR, and OR. All these thermal spin molecular Boolean logic gates contain metal atoms, providing the magnetic source of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, applying external magnetic fields in various directions on metal atoms within a narrow area is challenging. [25] On the contrary, owing to the rapid development of scanning probe technology, electric field regulation technology is relatively mature. Therefore, it is meaningful and necessary to find new thermal spin molecular Boolean logic gates, which are controlled only by the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…28 At present, many single molecules have been evaluated to have important application prospects in the field of molecular spintronics. 2,[29][30][31][32][33] For example, Yoshida et al studied C 60based transistors with ferromagnetic Ni leads, and observed a gate-tunable tunnel MR effect. 31 Petta et al investigated the transport properties of octanethiol coupled to Ni electrodes, and observed spin-polarized tunnel behavior in molecular tunnel junctions.…”
Section: Introductionmentioning
confidence: 99%